DINAMISASI DAN PRODUKTIVITAS PRIMER SUNGAI CITARUM PROVINSI JAWA BARAT - Anggi Suprabawati; Arie Hardian; Eki Al Ghifari (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
Monitoring the quality of the river is essentially to know the status of the periodic quality of the river. Good assessment of river water quality should use a combination of physical, chemical and biological parameters. One way that can be done to describe water quality in an area is the primary productivity in the water. Primary productivity is the amount of organic material produced by autotrophic organisms with the help of sunlight. Perifiton as a river microorganism, will provide dissolved oxygen (DO) through photosynthesis to maintain most of the life of the surrounding water, then Periphyton can respond quickly to environmental changes, this is an indicator of changing conditions (Gaiser 2008 and Lakewatch, 2000) in Brown and Wright (2016) Chemical reactions that occur in the aquatic environment also involve interactions between ions and other phases. Some important interactions in the waters are the occurrence of photosynthesis by algae and the exchange of dissolved solids with dissolved gases in water. The same exchange occurs when bacteria degrade organic matter (often in the form of particles) in water. Some important elements move around in aquatic systems as colloidal chemical compounds or are absorbed into soil particles. The equilibrium of physical chemical reactions in waters involves sediment, gas, and water. Sediment is a layer of material or material that covers the bottom of small rivers, lakes, reservoirs, bays, and oceans. Sediments contain fine mixtures and subtle minerals, including clay, silt, and sand, which mix with organic materials. These materials may experience changes in composition from pure mineral ingredients to main organic ingredients. Sediments contain biological ingredients, chemicals, and pollutants in water. Keywords: Primary Productivity; citarum river ; sediment; water test parameter